Uninettuno University for Refugees: a Model of Network for an Education without Boundaries - Garito, Maria Amata (Advances in Social Sciences Research Journal, 2020)
In the European countries, and especially in Italy, one of the hardest challenges we are facing these days is the escalating crisis of migrants and refugees coming from the Arab World and Sub-Saharan Africa countries. The history of universities tells us that the first Universities realized a networked model in which students shaped their own study path, moving from one institution to another across Europe in order to attend the lectures by the best lecturers from different Universities. The Medieval higher education system, therefore, acted as a bridge between different cultures, fostering knowledge exchange, sharing and construction based on a networked organizational model, and an educational model promoting discussions and debates (questio and disputatio). Nowadays, ICT technologies, and above all the Internet, allow Universities to re-create a network of knowledge and of students and professors, sharing experiences and competences from different social and cultural backgrounds. The International Telematic University UNINETTUNO developed and implemented an internalization model and a psycho-pedagogic model, whose main characteristics are described in this paper, promoting the collaboration among Universities from the United States, Europe, Asia and above all from the Arab World Countries. Through this collaborations, UNINETTUNO developed the first higher education portal in the world which is available in 5 languages (Italian, English, French, Arabic and Greek), enrolled students from 168 countries of the world. The success of these international cooperation activities inspired UNINETTUNO in the creation of an Internet-based portal (The University for Refugees — Education without Boundaries, that will be presented in this paper) allowing refugees and migrants to access the University for free from any place across the world, providing services like: Recognition of the study title, Recognition of Professional Skills, Language Learning courses, Health Services, Mutual Rights and Duties. This initiative, launched in 2016, became a true laboratory of intercultural and interlingual communication that promotes a truly effective model of cooperation and inclusion with refugees and students from different parts of the world.